Quality of life in patients with hypopituitarism. Issue 4 (August 2015) - Crespo, Iris; Santos, Alicia; Webb, Susan M.
Abstract : Purpose of review: Quality of life (QoL) is impaired in patients with adults with growth hormone deficiency (AGHD) of any cause, especially if additional hypopituitarism is present, and improves after replacement therapy with recombinant human growth hormone (rhGH). This review includes relevant publications since 2013. Recent findings: Recent findings confirm that most patients with AGHD who improve their QoL after rhGH therapy experience persistent effects for years, if replacement therapy is maintained. Sometimes, however, QoL may not normalize completely, especially if it is caused by a craniopharyngioma (because of concomitant neuropsychological comorbidities that affect autonomy and cognitive function), or functional pituitary tumours, i.e., in Cushing's disease, in which chronic brain exposure to hypercortisolism is associated with more depression, anxiety, loss of memory and emotional distress. Another group in which QoL and energy rarely normalize despite improving after rhGH is hypopituitarism because of traumatic brain injury. Worse QoL is seen in patients who also suffer insomnia, depression, negative illness perceptions and are treated in a rural (compared with an urban) healthcare environment. Better QoL after rhGH is seen in AGHD patients who are not depressed, after successful surgery, living in Europe (rather than the USA), with poorer baseline QoL scores, less obesity and no impaired vision. Summary: Further improvement of QoL may be possible with individualized psychosocial interventions.